Mechanism for Investing in Sponsorship Rights for Youth Football Players in Professional Clubs - Wissam Hameed Ali; Ali Fawzi Ahmed; Aseel Ibrahim Shehab (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The research aims to develop mechanisms for investing in the sponsorship rights of young football players for professional clubs in Iraq by identifying (the importance of nurturing and developing talented people in football, applying scientific innovations in developing and nurturing talent to create young professional players in football in a professional manner and culture, motivating investors to establish investment companies in the field Sponsoring and nurturing football players in sports bodies and academies, commercial and media rights in nurturing and nurturing talent in football, the role of the state in providing development and investment projects, and ways and means of expanding the base for discovering and selecting talent in football. The researcher used the descriptive approach, and the research sample included a sample of (103) members of the boards of directors of some clubs, some employees of the Ministry of Youth and Sports, and a group of investors and businessmen interested in the sports field. One of the most important results was increasing the technical level of the national teams and helping to develop the clubs, providing external professional training for outstanding talents upon reaching the permissible age. To transfer abroad, 18 years through a marketing network to be supportive of the Iraqi teams